The Missing Link: Cre Pigs for Cancer Research - Kalla, Daniela; Flisikowski, Krzysztof; Yang, Kaiyuan; Sangüesa, Laura Beltran; Kurome, Mayuko; Kessler, Barbara; Zakhartchenko, Valeri; Wolf, Eckhard; Lickert, Heiko; Saur, Dieter; Schnieke, Angelika; Flisikowska, Tatiana (Frontiers in Oncology, 2021)
The Cre/loxP system is a powerful tool for the generation of animal models with precise spatial and temporal gene expression. It has proven indispensable in the generation of cancer models with tissue-specific expression of oncogenes or the inactivation of tumor suppressor genes. Consequently, Cre-transgenic mice have become an essential prerequisite in basic cancer research. While it is unlikely that pigs will ever replace mice in basic research they are already providing powerful complementary resources for translational studies. But, although conditionally targeted onco-pigs have been generated, no Cre-driver lines exist for any of the major human cancers. To model human pancreatic cancer in pigs, Cre-driver lines were generated by CRISPR/Cas9-mediated insertion of codon-improved Cre (iCre) into the porcine PTF1A gene, thus guaranteeing tissue and cell type-specific function which was proven using dual fluorescent reporter pigs. The method used can easily be adapted for the generation of other porcine Cre-driver lines, providing a missing tool for modeling human cancers in large animals.